LANDASAN FILOSOFIS DAN ASAS-ASAS DALAM HUKUM PENANAMAN MODAL DI INDONESIA - Hidayah, Ardiana (Faculty of Law, University of Palembang, 2018)
Pancasila as the philosophical foundation of the Indonesian nation which contains noble ideals and guidelines in the life of the nation and state in running the economy in Indonesia. This also influences economic development through investment activities. Investment arrangements in Indonesia are regulated in Law Number 25 of 2007 concerning Investment, that investment is carried out on the basis of: legal certainty; openness; accountability; equal treatment and does not differentiate national origin; togetherness; fair efficiency; sustainable; environmentally sound; independence; balance of progress and unity of the national economy